Contemporary Homo Europeicus. Transformation of European Identity - Zamojski, Adam (Respectus Philologicus, 2015)
This article explains the origins of European identity, contemporary Homo Europeicus and transformation of European identity. It describes, in a synthetic form, the symbolic sources of European identity like ancient Greek philosophy, Roman law, Christian religion, Barbarian aspects of civilisation and the Age of Enlightenment. It as well describes the circumstances and causes of the crisis of Latin civilization and traditional European Identity in relation to the population boom of Muslims in the Western Europe. Further on, it concludes with an outlook on the role of Postmodernism, Islam, Christian evolutionism, Neo-pagan religion, New Age Movement and Consumptionism in the transformation process of the traditional EuropeanIdentity. Conclusion is an attempt to exemplify the style of Andrzej Wierciński’s scientific approach. This part presents his concept of the peculiarity of the specific human nature which is polarized into the animal side versus the human potential.
Keywords: Homo Europeicus; European Identity; Genographic Project; Ancient Greece and Rome; Enlightenment; Postmodernism; Islamization; Teilhard de Chardin; Neo-pagan; New Age Movement; Consumptionism; Andrzej Wierciński; specific human nature; polarization of man; Christianity; Barbarity